Perancangan Sistem Informasi Inventory Barang Pada Bengkel Honda Berdikari Motor - Cucu Tri Ramdani; Muhammad Husen; Manasye Usfal; Thoyyibah T. (CV. Multi Kreasi Media, 2023)
Currently the development of information technology is growing rapidly and demands to create an application that can solve an existing problem but have not found a solution. In the process of knowing the amount of stock of goods sometimes will have difficulty if you have to check manually. Application at BENGKEL HONDA BERDIKARI MOTOR is based on the need for accurate information management in the management of goods status in the company. Before making this information system, the author designed the tables needed first in order to facilitate the manufacture. This information system is made by using PHP and MYSQL programing language as its database. The author use data flow diagram to design the system workflow scheme and ERD to create relationships between tables. The result of this research is to create a web-based inventory and speed up the process of delivering inventory information